5 Oral Administration of Branched-Chain Amino Acids Results in Increased Seizure Threshold and Loss of Hippocampal Neurons in a Rodent Model of Mesial Temporal Lobe Epilepsy. (11th January 2018) - Gruenbaum, Shaun; Dhaher, Roni; Rapuano, Amedeo; Tang, Amber; Eid, Tore
Abstract: The objective of this study was to determine the effects of oral supplementation with branched-chain amino acids (BCAAs) leucine, isoleucine, and valine on seizures and neuronal viability in a rodent model of mesial temporal lobe epilepsy (MTLE), a common form of medication-refractory focal epilepsy. Sixteen rats were randomly divided into two groups: eight rats drank a 4% aqueous solution of all three BCAAs (BCAA group) ad libitum for 31 days, and the other eight rats drank regular water (control group) for the same period. After 10 days of drinking, a microinfusion cannula was surgically implanted in the right dentate gyrus to continuously infuse the glutamine synthetase inhibitor methionine sulfoximine (MSO) at a rate of 0.625 ug/hr for 28 days. The frequency of spontaneous seizures was analyzed via continuous video and electroencephalogram (EEG) monitoring for 21 days. To assess seizure threshold, all rats were then administered a single intraperitoneal injection of 40 mg/kg pentylenetetrazole (PTZ), a GABA antagonist. Rats were monitored for time to twitch, time to convulsions, and time interval between twitch and convulsions. After 31 days of drinking, rats were perfused transcardially with 0.9% NaCl followed by 4% formaldehyde in phosphate buffer. The brains were removed and fixed, sectioned on a Vibratome at 50 um thickness, and mounted on a gelatin-coated slides and stained with NeuN. Neuron counts in the hilar region were performed ipsilateral and contralateral to the infusion site using a stereological technique. No significant differences were found between BCAA rats and control rats with respect to the frequency or severity of spontaneous seizures in weeks 1, 2, or 3. After injection of PTZ, BCAA rats had an increased time to twitch (88.2 ± 20.9s vs 44 ± 10.9s, P = .07), convulsions (174.6 ± 17.26s vs 51.9 ± 14.6s, P < .05), and interval between twitch and convulsions (86.8 ± 42.8s vs 7.9 ± 4.4s, P = .05) compared with control rats. Rats in the BCAA group had 37% fewer neurons in the ipsilateral dentate hilus than the control group (5.8 x 10 –4 ± 6.8 x 10 –5 vs 8.9 x 10 –4 ± 5.6 x 10 –5 cells respectively, P < .01), and 39% fewer neurons in the contralateral dentate hilus than the control group (5.0 x 10 –4 ± 5.8 x 10 –5 vs 7.0 x 10 –4 ± 3.4 x 10 –5 cells respectively, P = .01). This study demonstrated the effects of chronic BCAA ingestion on spontaneous and induced seizures in a translationally-relevant rodent model of MTLE. Chronic BCAA ingestion was effective in increasing the seizure threshold to PTZ-induced seizures, but was ineffective in reducing the frequency or severity of spontaneous seizures in GS-inhibited, epileptic rats. Importantly, chronic BCAA ingestion aggravated the hilar neuron loss, which may have important implications for humans and should be further evaluated.